2015
DOI: 10.3389/fpsyg.2014.01572
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness training for reducing anger, anxiety, and depression in fibromyalgia patients

Abstract: Fibromyalgia is a disabling syndrome. Results obtained with different therapies are very limited to date. The goal of this study was to verify whether the application of a mindfulness-based training program was effective in modifying anger, anxiety, and depression levels in a group of women diagnosed with fibromyalgia. This study is an experimental trial that employed a waiting list control group. Measures were taken at three different times: pretest, posttest, and follow-up. The statistical analyses revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
62
1
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 24 publications
13
62
1
11
Order By: Relevance
“…This is consistent with other research teams that found a diminution of state, trait, or overall anxiety after treatments using mindfulness meditation 16, 31, 32. This is due to individuals at practicing mindfulness may learn to keep a relaxed mind and focus on present moment, cultivating an attitude of acceptance and patience toward unpleasant emotions and thoughts that may arise 32 …”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with other research teams that found a diminution of state, trait, or overall anxiety after treatments using mindfulness meditation 16, 31, 32. This is due to individuals at practicing mindfulness may learn to keep a relaxed mind and focus on present moment, cultivating an attitude of acceptance and patience toward unpleasant emotions and thoughts that may arise 32 …”
Section: Discussionsupporting
confidence: 90%
“…Second, MBAT predicted lower volatility of anger than both CBT and UC. Although no known research has examined the effects of mindfulness treatment on volatility, dispositional mindfulness predicts lower volatility of negative affect (Adams et al, 2014), and mindfulness training shows promise for reducing anger (e.g., Amutio et al, 2014). Mindfulness meditation may promote “metacognitive awareness,” or “decentering,” whereby individuals learn to view thoughts and feelings as mental events rather than facts (Bishop et al, 2004; Teasdale et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This effect was not detected in the HLT group [79], suggesting that mindfulness techniques may uniquely exert increased effectiveness in patients diagnosed with concurrent depression. Interestingly, a separate study examined the efficacy of 7 weeks of mindfulness training in comparison to a wait-list control on depression, anger, and anxiety in fibromyalgia patients [80]. Mindfulness training incorporated aspects of MBSR but was similar to MSER in that it was modified to focus on acceptance of emotions, thoughts, and sensations.…”
Section: Mindfulness Meditation and Fibromyalgiamentioning
confidence: 99%